Doubling the Dose of Bevacizumab Beyond Progression in Metastatic Colorectal Cancer–the Experience of a Tertiary Cancer Center - Căinap, Călin; Bochiş, Ovidiu-Vasile; Vlad, Cătălin; Popita, Raluca; Achimaş-Cadariu, Patriciu; Havasi, Andrei; Vidrean, Andreea; Dranca, Alexandra; Piciu, Andra; Constantin, Anne-Marie; Tat, Tiberiu; Dana, Maniu; et al. (Frontiers in Pharmacology, 2021)
Background: Colorectal cancer (CRC) is the third most common cancer in Europe, with an annual increase in incidence ranging between 0.4% and 3.6% in different countries. Although the development of CRC was extensively studied, no new therapies have been developed in the last few years. Bevacizumab is frequently used on a daily basis both as first- and second-line therapy. International guidelines offer available treatment options but they cannot answer all the questions raised in clinical practice when treating metastatic CRC patients outside clinical studies. Methods: We carried out a retrospective analysis of consecutive patients with confirmed metastatic colorectal cancer (mCRC) treated with bevacizumab at "Prof Dr Ion Chiricuta" Institute of Oncology, Cluj-Napoca. We selected patients who received bevacizumab both in first- and second-line therapy and stratified them according to the bevacizumab dose administered in the second line. In each group, we evaluated the prognostic factors that influenced survival and treatment response. Results: We included 151 patients who received bevacizumab beyond progression. The median age of patients was 58 in the double dose bevacizumab (DDB) group and 57 in the same dose bevacizumab (SDB) group. The median overall survival in the DDB group was 41 months compared with 25 months in the SDB group (p = 0.01 log-rank test). First-line oxaliplatin-based treatment was used more frequently regardless of group, while irinotecan-based treatment was more frequent in the second line (p=0.014). Both oxaliplatin- and irinotecan-based regimens seemed to be suitable partners for bevacizumab beyond progression. Statistical analysis revealed the significance of dose intensity, primary tumor location and cumulative exposure to bevacizumab beyond progression. Conclusions: Doubling the dose of bevacizumab after first progression could improve survival in mCRC. Increasing bevacizumab dose intensity could overcome the prognostic influence of primary tumor location in patients receiving double dose bevacizumab after first disease progression.